A drug-self-gated and tumor microenvironment-responsive mesoporous silica vehicle: "four-in-one" versatile nanomedicine for targeted multidrug-resistant cancer therapy. Issue 43 (31st October 2017) - Cheng, Wei; Liang, Chaoyu; Wang, Xusheng; Tsai, Hsiang-i; Liu, Gan; Peng, Yunmei; Nie, Junpeng; Huang, Laiqiang; Mei, Lin; Zeng, Xiaowei
Abstract : A smart nanoplatform which co-delivers doxorubicin and P-gp siRNA exhibited an excellent synergistic effect for targeted multidrug-resistant cancer therapy. Abstract : The design of multifunctional nanocarriers for the co-delivery of anticancer drugs and genetic agents offers an effective and promising strategy to combat multidrug-resistant cancer. Herein, we developed a simple and facile method to fabricate a drug-self-gated and pH-sensitive mesoporous silica vehicle as a "four-in-one" versatile co-delivery system, which possesses targeted chemo and gene therapy capability against multidrug-resistant cancer. P-gp siRNA molecules were loaded into the channels of mesoporous silica nanoparticles. A chemotherapeutic drug (DOX) was employed as a gatekeeper via a pH-sensitive benzoic–imine covalent bond. Folic acid conjugation onto the surface endowed this system with an excellent tumor-targeting effect, which was demonstrated by the cellular and tumor targeting assay. The effective downregulation of P-gp protein by the co-delivered P-gp siRNA was observed by western blotting. Both the in vitro cell viability study and in vivo tumor inhibition assay showed a synergistic effect in suppressing cancer cell proliferation. Therefore, this drug-self-gated nanosystem exhibited great potential for improved multidrug-resistant cancer treatment without any further potential risks of capping agents.